Исследование течения нелинейно-вязкой жидкости в частично-заполненном вращающемся цилиндре методом граничных элементов - Мамазова, Дилара Абдурасуловна (Перспективы развития фундаментальных наук. Т. 1 : сборник научных трудов XVII Международной конференции студентов, аспирантов и молодых ученых, Россия, Томск, 21-24 апреля 2020 г.)
The flow of a liquid that partially fills a horizontal cylinder rotating at constant velocity is considered. A problem is mathematically formulated in the creeping-flow approximation and is numerically solved by the boundary-element method. In the course of the work, the free surface forms for the kinematic condition in Eulerian and Lagrangian forms with different values of the number W and duty cycle X, which characterize the motion of the fluid inside the rotating cylinder, were presented. The rimming flow of a thin film inside a rotating horizontal cylinder is studied.